Pelatihan Manajemen Sistem Informasi Digital dalam Meningkatkan Mutu Layanan di Pondok Pesantren Lubabul Fattah Tunggulsari Kabupaten Tulungagung - Mutohar, Prim Masrokan; Darmawan, Dendys; Prastiwi, Meilinda Ade (Universitas Nusantara PGRI Kediri, 2025)
Information systems play a very important role in supporting the improvement of service quality in the current digital era, namely acting as the main foundation in service transformation, both in the public and private sectors. The challenges in managing administration and services at the Lubabul Fattah Tunggulsari Islamic Boarding School are still dominated by manual systems that are less efficient, resulting in delays in data processing, inaccuracy in managing information, and lack of transparency in Islamic boarding school management. This training is designed by providing practical guidance and technical simulations that can be implemented directly. This study uses the Participatory Action Research (PAR) method, which emphasizes the active involvement of participants in the process of identifying problems, designing solutions, and implementing and evaluating digital information system management training. The results obtained were an increase in participants' understanding and skills related to the use of digital information systems, especially the SIPonpes application, to support the management of administration and operations of Islamic boarding schools. Participants succeeded in integrating digital technology into their work processes, which include student data management, learning schedule management, and automatic creation of administrative and financial reports. Another result was the improvement of digital infrastructure through technical solutions provided to overcome obstacles during implementation, such as troubleshooting guides and direct technical assistance by the implementation team. Overall, this activity has succeeded in bringing about real positive changes in the modernization of Islamic boarding school services, while also providing a digital management model that can be replicated in other institutions.